Hubungan Kelengkapan Sistem Fire Safety, Pengetahuan Dan Sikap Pegawai Dengan Kesiapsiagaan Risiko Kebakaran Di Rumah Sakit Umum Daerah Tamansari Jakarta Barat - Riyan Pangestu; Rahmat Supriyatna; Achmad Lukman Hakim (Jurnal Ilmu Kesehatan dan Gizi, 2023)
The hospital is a workplace that is very loaded with potential hazards to the health and safety of its workers, one of the hazards is fire. The risk of fire in hospitals has a fairly high level of danger compared to other places. Therefore, a fire management system is needed that can prevent and deal with fires such as management policies, organization and procedures, identification and analysis of fire risks, evaluation of fire risks, coaching and training, fire protection facilities. The purpose of this study is to analyze the relationship between perceptions of the completeness of the fire safety system, knowledge and attitudes with fire risk preparedness at Tamansari West Jakarta Hospital in 2023. This type of research is an analytic survey with a cross sectional approach. This research was conducted in August 2022─May 2023 at Tamansari Hospital, West Jakarta. The population of this study are employees who work in Tanabsari Hospital services. With the Slovin formula, the research sample was obtained, namely 114 respondents with the sampling technique used, namely purposive sampling. This study used the chi square statistical test using SPSS 22. The validity and reliability of the questionnaire was tested on 10 respondents who were estimated to have good insight and in accordance with the theme studied in January 2023. The results showed that fire risk preparedness with statistical test results obtained a value continuity correction 1,000, knowledge obtained a value of 0.000 and attitude obtained a value of 0.023 (p-value <0.05). This value states that there is a significant relationship between knowledge and attitudes and fire risk preparedness, but there is no relationship between the completeness of the fire safety system and fire risk preparedness. It is hoped that they will be able to take part in Building Fire Safety Management training in order to increase their knowledge and attitude in fire emergency evacuation.